The Effects of Interest Rate on Financial Growth of Banks in Uganda. - Victor Cedric Sekitoleko (Uganda Christian University, 2023)
The study was carried out to assess the effects of interest rate on financial growth of banks in Uganda at DFCU Bank, Hoima Branch. The objectives of the study were to identify how interest rates affect performance, to ascertain how operational efficiency affects performance and to ascertain how profitability affects performance. The research design was qualitative and quantitative in nature in which the qualitative design was used because it investigates the qualities of relationship, situations, activities and matters as referred to the case study. Quantitative design was used because analyzes the particular figures in regards to the study objectives. Questionnaires and interview guides were used to collect data on a sample population of 50 respondents that included Bank Manager, Accountant/Auditor, Tellers, Customer Service Personnel and customers. The findings revealed that customers at the bank have access to loans and only customers who meet the loan requirements can access the loans they applied for. However those that do not have access to loans do not have the loan requirements/collateral security. High interest rates can help banks recover and enhance their balance sheets and performance by leading to capital gains, supporting asset prices and reducing non-performing loans. But persistently high interest rates – “high for long” – may also erode the profitability and franchise value of banks, because high rates are typically associated with high net interest margins (NIMs). Banks will often be reluctant to (quickly) increase lower deposit rates as interest rates decline, especially for retail depositors. In a nutshell, DFCU Hoima branch is one of the numerous branches of Uganda’s fast growing bank. The bank offers loans to its clients as a core activities at easily affordable rates as stipulated in their loan repayment plans and has heavily invested in Information technology equipment’s to ensure that it has a sound performance. However, despite all these, the market forces of demand and supply in Uganda’s dynamic economy have led to instances of loans defaults basing on the interest and loan repayment periods and as thus, its performance is always being affected. The study thus recommended that loan repayment periods should be revised to start from 6 years and above, this should also go hand in hand with interest rates that are 23% for long term loans and 21% for short term loan. However, a standard interest rate figure should be revised, a loan appraisal should be undertaken on each and every client to ensure that a client knows the implications of loan defaults, clients who have had setbacks in business should always meet the bank and explain their stand to ensure that the bank can increase on their loan repayment period, appraisals should be carried out on a monthly basis other than on a quarterly basis to ensure that there is room for improvement and that anything that goes wrong does not happen again.
This is a dissertation.